Prognostic role of neutrophil‐to‐lymphocyte ratio in head and neck cancer: A meta‐analysis. Issue 3 (27th October 2017) - Takenaka, Yukinori; Oya, Ryohei; Kitamiura, Takahiro; Ashida, Naoki; Shimizu, Kotaro; Takemura, Kazuya; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract: Background: Neutrophils play substantial roles in cancer progression. Previous reports demonstrated the prognostic impact of the pretreatment neutrophil‐to‐lymphocyte ratio (NLR) in various types of solid cancers. The purpose of this study was to quantify the prognostic impact of NLR on head and neck squamous cell carcinoma (HNSCC). Methods: We systematically searched electronic databases, identified articles regarding NLR and HNSCC mortality, and extracted hazard ratios (HRs) and 95% confidence intervals (CIs). Pooled HRs for overall survival (OS) and disease‐specific survival (DSS) were estimated using random effect models. Results: Nineteen studies enrolling 3770 patients were included in the analyses. Overall, NLR greater than the cutoff value was associated with poorer OS and DSS (HR 1.69; 95% CI 1.47‐1.93; P < .001 and HR 1.88; 95% CI 1.20‐2.95; P = .006, respectively). Conclusion: Elevated NLR predicts worse outcomes in patients with HNSCC.